The 5th Southeast Asia Radiographers and Radiological Technologists Conference The 6th Scientific Meeting of Indonesian Society of Radiographers - Redaksi ([s.n.], 2018)
The 5th Southeast Asia Radiographers and Radiological Technologists Conference The 6th Scientific Meeting of Indonesian Society of Rodiographers